Parity of concepts «children of street», homeless, neglected, social orphans and children, deprived parental care - Тимкович, Ірина Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In clause to be spent the comparative characteristic of concepts «children of street», homeless, neglected, socialorphans and children, deprived parental care. The author does a conclusion, that homeless children simultaneously concern to all set forth above categories.